The role of self-efficacy in mediating the effect of selfleadership and knowledge sharing towards innovative work behaviour in private higher education institutions - Ibus, Salbeha (2021)
Innovative work behavior is crucial to achieve a long-term survival and sustainability for organizations inclusive Higher Education Institutions. Numerous studies indicated that self-leadership and knowledge sharing are important predictor on innovative work behavior. However, the study which focused on the effect of self- leadership and knowledge sharing on innovative work behavior is still scarce especially in the context of Malaysian educational sector. Thus, this research aims to investigate how selfleadership